Intramuscular adipose tissue in the quadriceps is more strongly related to recovery of activities of daily living than muscle mass in older inpatients. Issue 4 (16th May 2021) - Akazawa, Naoki; Kishi, Masaki; Hino, Toshikazu; Tsuji, Ryota; Tamura, Kimiyuki; Hioka, Akemi; Moriyama, Hideki
Abstract: Background: The relationship between intramuscular adipose tissue at admission and recovery of activities of daily living (ADL) remains unclear. This study aimed to examine the relationship between intramuscular adipose tissue in the quadriceps at admission and recovery of ADL in older inpatients. Methods: This prospective study included 404 inpatients aged ≥65 years (54.7% female). Recovery of ADL during hospital stay was assessed using the Barthel Index (BI) score at discharge, BI score change, and BI efficiency. Higher BI at discharge, BI score change, and BI efficiency indicate more improvement in ADL. Intramuscular adipose tissue and muscle mass of the quadriceps were assessed using echo intensity and muscle thickness on ultrasound images, respectively. Multiple regression analysis was performed to identify factors independently associated with BI score at discharge, BI score change, and BI efficiency. The independent variables were BI score at admission, echo intensity and muscle thickness of the quadriceps, age, sex, number of medications, C‐reactive protein concentration, updated Charlson Comorbidity Index score, Food Intake Level Scale, Geriatric Nutritional Risk Index score, days from onset disease, length of hospital stay, number of units of rehabilitation therapy, and subcutaneous fat thickness of the thigh. Results: The medians (inter‐quartile range) of the BI score at discharge, BI score change, and BI efficiency were 60.0 (35.0–80.0), 10.0 (0.0–25.0), and 0.11 (0.00–0.37), respectively. The median (inter‐quartile range) of the length of hospital stay (days) and days from onset disease were 58.0 (39.0–92.0) and 79.0 (49.0–112.0), respectively. Quadriceps echo intensity was independently and significantly associated with the BI score at discharge ( β  = −0.13, P  < 0.01), BI score change ( β  = −0.23, P  < 0.01), and BI efficiency ( β  = −0.21, P  < 0.01). Quadriceps thickness was not independently and significantly associated with the BI score at discharge ( β  = −0.02, P  = 0.68), BI score change ( β  = −0.02, P  = 0.79), and BI efficiency ( β  = 0.03, P  = 0.67). Conclusions: Our study indicates that greater intramuscular adipose tissue in the quadriceps at admission is more strongly related to worse recovery of ADL than less muscle mass in older inpatients. Greater intramuscular adipose tissue in the quadriceps in older inpatients is considered to be a predictor of worse recovery of ADL, and intervening for greater intramuscular adipose tissue may be important for improving ADL in older inpatients.